Conceptual design of a hybrid propulsion underwater robotic vehicle with different propulsion systems for ocean observations. (15th June 2019) - Kadiyam, Jagadeesh; Mohan, Santhakumar
Abstract: The proposed design named as the hybrid propulsion underwater robotic vehicle (HPURV) is a novel underwater vehicle with a hybridized propulsion for minimum energy consumption in ocean observations. This development is aimed at the comparison of different types of propulsion techniques in both vertical and horizontal directions of the motion to choose an optimum strategy for propulsion. The horizontal motion is achieved using the bio-inspired method of fish propulsion using caudal fin or a pair of pectoral fins or both. The tail design is made modular such that the caudal fin can be replaced by a conventional miniature thruster to understand the performance characteristics of the vehicle under similar operating conditions. The diving/climbing, pitching and rolling motions are achieved using three different mechanisms for, viz., (1) pitch and dive using pectoral fins, (2) pitch and dive by varying buoyancy of the vehicle and (3) pitch, dive, and roll by using a moving mass and a rolling mass mechanisms, respectively. All these mechanisms are assembled in the same vehicle and controlled independently or using a combination of two or more different mechanisms for the performance comparison of the vehicle in similar operating conditions. This paper also presents a dynamic model of the HPURV and a motion control scheme using a conventional Proportional-Derivative (PD) control technique to track a given complex spatial trajectory. Highlights: Inspired from boxfish carapace for both stability and maneuverability implemented with hybrid propulsion strategy. Three different propulsion modes, viz., a vertical profiler mode, an underwater vehicle mode and an underwater glider mode. Proposed vehicle design operates in both autonomous and semi-autonomous modes. Modular and redundant design for failsafe operations during emergency conditions. Single fin propulsion for simple design and operation for long term operation.